Prognosis of heart failure with preserved ejection fraction treated with β-blockers: A propensity matched study in the community. (1st November 2016) - Ruiz, Gema; Andrey, Jose L.; Puerto, Jose L.; Escobar, Miguel A.; Romero, Sotero P.; Aranda, Rocio; Pedrosa, María J.; Gomez, Francisco
Abstract: Background: The effect of treatment with β-blockers on the prognosis of patients newly diagnosed with heart failure with preserved ejection fraction (HFpEF) is unknown. Objective: To analyze the relationship of commencing treatment with the β-blockers bisoprolol or carvedilol (CT-βB) with the prognosis of newly diagnosed HFpEF. Methods: Prospective study over 10 years on 2704 patients with HFpEF. Main outcomes were mortality (all-cause and cardiovascular), hospitalizations for HF worsening, and visits. The independent relationship between CT-βB and the prognosis, stratifying patients for cardiovascular co-morbidity after propensity score-matching (985 patients CT-βB vs. another 985 patients non-CT-βB), was analyzed. Results: During a median follow-up of 1877.4 days (interquartile range, 1–3651.2) 1600 died (81.2%), and 1702 were hospitalized (86.4%). CT-βB was associated with a lower risk of mortality (all-cause: HR [CI 95%] 0.78 [0.71 to 0.85], and cardiovascular: 0.75 [0.69 to 0.82]), a lower hospitalization rate (per 100 persons-year), 15.8 vs. 19.2, and a lower 30-day readmission rate (per 100 persons-year), 4.0 vs. 5.8, ( P < 0.001 in all cases), even after adjustment for the propensity to take β-blockers or other medications, comorbidities, and other potential confounders. These effects of CT-βB were independent of gender, and were observed in both patients taking high dose βB (over the median dose) and lower dose βB (under or equal to the median dose). Conclusions: In this propensity matched study, commencing treatment with bisoprolol or carvedilol, both at high and at lower doses, is associated with an improved prognosis of patients newly diagnosed with HFpEF.